1993
DOI: 10.1139/y93-006
|View full text |Cite
|
Sign up to set email alerts
|

Energy-dependent transport of digoxin across renal tubular cell monolayers (LLC-PK1)

Abstract: Digoxin secretory transport across renal tubular cell monolayers (LLC-PK1) grown on permeable filters was characterized. Metabolic inhibitors reduced total and specific basolateral to apical (B-A) flux of digoxin and conversely increased the apical to basolateral (A-B) flux. The specific transport of digoxin from the basolateral to the apical compartment was saturable, with a maximum velocity of transport of 184.5 +/- 38.0 pmol.cm-2.h-1 and a Michaelis-Menten constant (Km) of 14.1 +/- 1.6 microM. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…of lipophilic steroids (van Kalken et al, 1993), digoxin (Ito et al, 1993) or colchicine (Speeg & Maldonado, 1994). Therefore, potential overlapping specificities at the p-glycoprotein transport level in epithelial tissues should be considered when cyclosporins are given together with other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…of lipophilic steroids (van Kalken et al, 1993), digoxin (Ito et al, 1993) or colchicine (Speeg & Maldonado, 1994). Therefore, potential overlapping specificities at the p-glycoprotein transport level in epithelial tissues should be considered when cyclosporins are given together with other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The half-saturation constant (K m ) for inhibition of mouse oatp2 being 5.7 μ m (21), digoxin is also a substrate of P-gp, the concentration used in these experiments is well above the K m for inhibition of P-gp (14.1 ± 1.6 μ m ) (31). For these studies, n = 10–14 wild-type mice were used for the [ 3 H]cortisol experiments, and n = 14–26 wild-type mice were used for the [ 3 H]corticosterone experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Ito et al found that the digoxin transport (200 nM) across renal tubular cells is a saturable (K m ¼ 14.1AE 1.6 mM), energy dependent process, because 2,4-dinitrophenol (1 mM) and sodium azide (10 mM) significantly reduced the b ! a flux (Ito et al 1993a). Moreover, inhibitors of P-glycoprotein (quinidine, verapamil and vincristine) significantly increased the a !…”
Section: Affinity To P-glycoprotein In Vitro and In Animal Studiesmentioning
confidence: 96%